Ginkgo biloba extract ameliorates ischemia reperfusion-induced renal injury in rats - VELİOĞLU ÖĞÜNÇ, AYLİZ; ŞENER, GÖKSEL; ÇETİNEL, ŞULE; ŞENER, TARIK EMRE (ACADEMIC PRESS LTD ELSEVIER SCIENCE LTD, 2005)
There is increasing evidence to suggest that reactive oxygen metabolites (ROMs) play a role in the pathogenesis of ischemia/reperfusion injury (I/R) in the kidney. This study was designed to determine the possible protective effect of Ginkgo biloba extract (EGb) on renal ischemia/reperfusion (I/R) injury. Wistar albino rats were unilaterally nephrectomized, and 15 days later they were subjected to 45 min of renal pedicle occlusion followed by 6h of reperfusion. Ginkgo biloba extract (EGb) (50mg kg(-1) day(-1)) or saline was administered twice, 15 min prior to ischemia and immediately before the reperfusion period. At the end of the treatment period, all rats were decapitated. Kidney samples were taken for histological examination or detennination of the renal malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and collagen content. Production of reactive oxidants was monitored by chemiluminescence (CL) assay. Creatinine and urea concentrations in blood were measured for the evaluation of renal function. Tumor necrosis factor-alpha (TNF-alpha) and lactate dehydrogenase (LDH) were also assayed in serum samples. Ischemia/reperfusion caused a significant decrease in GSH level, which was accompanied with significant increases in MDA level, MPO activity and collagen content of kidney tissues. Similarly, serum BUN and creatinine levels, as well as LDH and TNF-alpha, were elevated in the I/R group as compared to control group. On the other hand, EGb treatment reversed all these biochemical indices, as well as histopathological alterations, which were induced by I/R. The findings imply that ROMs play a causal role in I/R-induced renal injury and EGb exerts renoprotective effects probably by the radical scavenging and antioxidant activities. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: renal injury; ischemia/reperfusion; Ginkgo biloba; FREE-RADICALS; NITRIC-OXIDE; EGB 761; MYELOPEROXIDASE ACTIVITY; OXIDATIVE STRESS; TISSUE-INJURY; IN-VIVO; ISCHEMIA/REPERFUSION; MECHANISMS; MELATONIN